Freedom of expression - Oljana HOXHAJ (Juridical Tribune, 2013)
In this paper "Freedom of expression" I’ ve tried to explain the close relationship between freedom right and other constitutional freedoms, which have a direct impact on values consolidation in a democratic society and giving possibilities for the public to be active in the decision making process. The researches are based in three directions: the doctrine of international low, in Albanian literature; in native and foreign legislation and also in jurisprudence of Albanians courts and the European Court of Human Rights. The theme dedicates a wide space freedom of expression in the context of public debate, thereby guaranteeing the public's right to know. Many cases of interference in freedom of expression, has been given special importance in legal terms. This intervention must have a legitimate purpose to protect more than one of the public interests. All of this work focuses on sharing the idea that everyone has the right to freedom of opinion and expression; this right includes freedom to hold opinions without interference, receive and impart information and ideas through any media and regardless of frontiers.